EXPLORING STUDENTS’ PRACTICES AND PERCEPTIONS OF IMPLEMENTING GENRE-BASED LEARNING (GBL) IN DIFFERENTIATED LEARNING FOR WRITING SKILL DEVELOPMENT (INFERENCE: Journal of English Language Teaching, 2026)
This qualitative study examines students' practices, perceptions, and challenges in learning English writing through Genre-Based Learning (GBL) and Differentiated Instruction (DI) in two Senior High Schools in Bekasi Regency. Using classroom observation and semi-structured interviews with twenty students, the research explores how genre writing steps, model texts, and differentiated tasks support the development of writing skills. The findings indicate that GBL and DI help students understand text structure, construct clearer sentences, and generate ideas more effectively. Students perceived the instructional guidance as clear and supportive, and reported increased motivation when writing tasks were varied, collaborative, and aligned with their ability levels. However, students also experienced difficulties, including limited vocabulary, grammatical challenges, spelling errors, and adjusting to different writing genres. To overcome these barriers, they employed various strategies, including using dictionaries, searching for examples online, and seeking assistance from teachers or peers. This study provides practical implications for English teachers to integrate structured guidance and differentiated support in writing lessons. It also contributes to existing literature by demonstrating how GBL and DI can enhance writing competence and learner engagement in the Indonesian EFL high school context.
Keywords: Genre-Based Learning; Differentiated Instruction; Practice; Perception; Writing Skills